Оценка применения высокоскоростных массообменных аппаратов для ректификации смеси бензол-толуол - Куделя, А. А.; Киселёв, В. М.; Лаврова, Инна Олеговна (НТУ "ХПИ", 2013)
Наведено розрахунок і порівняння показників бензольно-толуольних ректифікаційних колон з насадкою Mellapac-250Y та високошвидкісної колони з КСЕ. Отримані дані про збільшення зйому продукту з одиниці об'єму апарату на 29 % при переході на ректифікаційну колону з контактно-сепараційними елементами. Описано ефект падіння ефективності насадки Mellapac-250Y при зростанні діаметра і відсутність такого ефекту для колон з використанням КСЕ.

The calculation and comparison of the benzene-toluene distillation columns with Mellapac-250Y and CSE are approved. The data of removal of per unit volume of the apparatus by 29 % during the transition to a distillation column contact and the separating element increasing are obtained. the of the. Falling of the pack efficiency with diameter increasing effect with Mellapak using and it absence with CSE is described.
Hight-speed mass-transfer apparatus application for benzene-toluene rectification
Keywords: масообменные процессы; массообменные аппараты; массообмен; осевой завихритель; газожидкостные сепараторы; массообменные колонны